Exploring the potentials of some compounds from Garcinia kola seeds towards identification of novel PDE‐5 inhibitors in erectile dysfunction therapy. (4th May 2021) - Ojo, Oluwafemi Adeleke; Ojo, Adebola Busola; Maimako, Rotdelmwa Filibus; Rotimi, Damilare; Iyobhebhe, Matthew; Alejolowo, Omokolade Oluwaseyi; Nwonuma, Charles Obiora; Elebiyo, Tobiloba Christaina
Abstract: Erectile dysfunction (ED) is one of the main challenges occurring among men worldwide, and is characterised by trouble getting or keeping steady erection during sexual intercourse. Various drugs like sildenafil, a phosphodiesterase‐5 inhibitor (PDE‐5) are freely available in the pharmacies, though normally associated with several adverse. This study was designed to assess the molecular relations obtainable between catechin, garcinal, garcinoic acid and d‐tocotrienol compounds isolated from Garcinia kola and targeted receptor linked to ED. These processes include the molecular docking of catechin, garcinal, garcinoic acid, d‐tocotrienol, and sildenafil to receptor: PDE‐5 via AutoDock Vina. Following the docking of catechin, garcinal, garcinoic acid and d‐tocotrienol with the PDE‐5‐receptor protein, we observed that all are protein inhibitors with garcinoic acid showing better binding affinity −10.0 kcal/mol with PDE‐5 receptor relevant to ED. Hence, the results provided insights into the development of garcinoic acid as a replacement for present ED management, with further analysis worth considering.